2020
DOI: 10.1111/1742-6723.13452
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence screening and response in New South Wales emergency departments: A multi‐site feasibility study

Abstract: ObjectiveTo test feasibility of a systematic approach to routine screening and response for intimate partner violence among women presenting to three New South Wales EDs.MethodsThis prospective feasibility study was conducted over 6 months in two rural and one major tertiary metropolitan ED in New South Wales. Women aged 16–45 years triaged category 3–5 (treat within 30 min/1 h/2 h), who could be approached privately, were screened for intimate partner violence using the validated HITS (Hurts, Insults, Threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…In this study, participants were asked if they had disclosed family violence concerns at any time-point during their involvement with the health service, not just a single or initial presentation. In the Spangaro et al 7 study, the 18% disclosure rate occurred in women screened on a single presentation to the emergency department at the health service. Spangaro et al also utilized the Hurts, Insults, Threatens and Screams or Swears (HITS) tool, which asks four questions designed to capture current/active intimate partner violence situations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In this study, participants were asked if they had disclosed family violence concerns at any time-point during their involvement with the health service, not just a single or initial presentation. In the Spangaro et al 7 study, the 18% disclosure rate occurred in women screened on a single presentation to the emergency department at the health service. Spangaro et al also utilized the Hurts, Insults, Threatens and Screams or Swears (HITS) tool, which asks four questions designed to capture current/active intimate partner violence situations.…”
Section: Discussionmentioning
confidence: 96%
“…The rates of disclosure of family violence concerns to hospital staff in this study are higher than those reported in a recent study of targeted screening in Australian emergency departments in the state of New South Wales. 7 However, the difference in the tools and time-point capture may have contributed to this variation. In this study, participants were asked if they had disclosed family violence concerns at any time-point during their involvement with the health service, not just a single or initial presentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations